2022
DOI: 10.1002/jbt.23126
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative brain and cerebellum injury induced byd‐galactosamine: Protective effect ofS‐methyl methionine sulfonium chloride

Abstract: The objective of this study was to examine the protective effects of S-methyl methionine sulfonium chloride (MMSC) against galactosamine (GalN)-induced brain and cerebellum injury in rats. A total of 22 female Sprague-Dawley rats were randomly divided into four groups as follows: Group I (n = 5), intact animals; Group II (n = 6), animals received 50 mg/kg/day of MMSC by gavage technique for 3 consecutive days; Group III (n = 5), animals injected with a single dose of 500 mg/kg of GalN intraperitoneally (ip); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…39 In some in vitro studies, vitamin U exhibited protective effect, such as in pentylenetetrazole-induced brain damage, 40 d-galactosamine-induced hepatotoxicity, 41 valproic acid-induced lens injury, 42 and in oxidative brain and cerebellum damage induced by d-galactosamine. 43 In the present research, vitamin B 6 exhibited the lowest IC 50 value for TrxR inhibition activity among tested vitamins. The amounts of vitamin B 3 , vitamin B 6 , vitamin C, and vitamin U required for 50% inhibition effects were 582.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…39 In some in vitro studies, vitamin U exhibited protective effect, such as in pentylenetetrazole-induced brain damage, 40 d-galactosamine-induced hepatotoxicity, 41 valproic acid-induced lens injury, 42 and in oxidative brain and cerebellum damage induced by d-galactosamine. 43 In the present research, vitamin B 6 exhibited the lowest IC 50 value for TrxR inhibition activity among tested vitamins. The amounts of vitamin B 3 , vitamin B 6 , vitamin C, and vitamin U required for 50% inhibition effects were 582.…”
Section: Discussionmentioning
confidence: 47%
“…Due to its sulfonium functional group, this cation is an intermediate in several metabolic processes 39 . In some in vitro studies, vitamin U exhibited protective effect, such as in pentylenetetrazole‐induced brain damage, 40 d ‐galactosamine‐induced hepatotoxicity, 41 valproic acid‐induced lens injury, 42 and in oxidative brain and cerebellum damage induced by d ‐galactosamine 43 . In the present research, vitamin B 6 exhibited the lowest IC 50 value for TrxR inhibition activity among tested vitamins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it protects the cerebral cortex from mitochondrial damage and oxidative stress ( 17 ). Mahmarzayeva et al ( 18 ) revealed that methionine metabolites could protect against galactosamine-induced encephalotoxicity by reversing the antioxidant enzyme content and antioxidant status levels. In addition, existing research has confirmed that heavy metal deposits, such as Pb and Ni, can lead to a reduction in the volume of the cerebral cortex.…”
Section: Discussionmentioning
confidence: 99%
“…6,[12][13][14][15][16] In addition, the most amazing and breath-taking attention of this sulfur containing compound is its antioxidant property, which has been proven by many researchers. [17][18][19] In the current study, the protective effects of MMSC on amiodarone induced brain damage was investigated.…”
Section: Introductionmentioning
confidence: 99%